Shocking Intimacy: Techniques, Technologies, and Aesthetics of Amplification in Clara Iannotta’s “Intent on Resurrection” (Sound Stage Screen, 2021)
“Certain sounds, even when they are loud or heard from close by, conjure small sources.” Small sounds, as Chion (2016) describes them in this quote, usually appear in intimate or contained settings, where their relatively low strength will not be spoiled by the masking effects of a noisy public sphere. What happens, however, when they are shared with an audience in a concert venue? Privileging a distributive understanding of agency, I explore the interactions of instruments, techniques, and processes through which the composer Clara Iannotta (b. 1983) brings small sounds to the public space of the concert hall in the first minute of her composition Intent on Resurrection – Spring or Some Such Thing (2014). By articulating the technological means harnessed to allow for the qualities of small sounds to emerge, I reveal the conditions that are required for sound to be recognized and experienced as intimate. Along the way, I draw connections between the amplification aesthetics of Iannotta’s work and Hyperrealist art, and theorize the concept of the “grain of the instrument” drawing on ideas from Roland Barthes, Pierre Schaeffer, and Brian Kane.
Keywords: small sounds; amplification; grain; mediation; affordances; intimacy; Hyperrealism